1992
DOI: 10.1159/000114122
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor and Sensory Mesencephalic Trigeminal Neurons in Lungfishes: Phylogenetic Implications

Abstract: The location and number of neurons in the brainstem with projections to the eye muscles were investigated by means of fluorescent tracers in the African lungfish Protopterus dolloi. The oculomotor nucleus (M III) projects bilaterally with a ratio of 3:1 (70 ipsilateral, 20 contralateral neurons). Three subdivisions of this nucleus can be differentiated: one projects exclusively ipsilaterally, another projects exclusively contralaterally, and a third component projects bilaterally. The trochlear nucleus (M IV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…In contrast, the situation found in Protopterus , with labeled fibers among the deep cellular tectal layer, resembles the condition found in anurans and reptiles . In both lungfishes studied, the large neurons of the mesencephalic trigeminal nucleus are easily recognized in the dorsal part of the tectum [von Bartheld, 1992] and do not show any particular relation to the orexin-ir fibers. Only in the rat is conspicuous innervation of the mesencephalic trigeminal nucleus described [Stoyanova and Lazarov, 2005].…”
Section: Distribution Of Orexin-ir Fibers In the Brain Of Vertebratesmentioning
confidence: 89%
“…In contrast, the situation found in Protopterus , with labeled fibers among the deep cellular tectal layer, resembles the condition found in anurans and reptiles . In both lungfishes studied, the large neurons of the mesencephalic trigeminal nucleus are easily recognized in the dorsal part of the tectum [von Bartheld, 1992] and do not show any particular relation to the orexin-ir fibers. Only in the rat is conspicuous innervation of the mesencephalic trigeminal nucleus described [Stoyanova and Lazarov, 2005].…”
Section: Distribution Of Orexin-ir Fibers In the Brain Of Vertebratesmentioning
confidence: 89%
“…All forms have a recognizable principal and accessory abducens, except some mammals that have secondarily lost the accessory abducens. [Compiled after Ariens-Kappers et al, 1936;Kishida et al, 1986;von Bartheld, 1992;Baker, 1993, 1995;Fritzsch et al, 1990;Fritzsch and Northcutt, 1993;Song and Boord, 1993;Szekely and Matesz, 1993;Wake, 1993;Fritzsch, 1998a, b].…”
Section: Discussionmentioning
confidence: 99%
“…The laterality of the trochlear motoneurons appears to be variable among vertebrates. In lamprey (Finger and Rovainen, 1979;Fritzsch et al, 1990), carp (Luiten and Dijkstra-de Vlieger, 1978), goldfish (Graf and McGurk, 1985), lungfish (von Bartheld, 1992), some amphibians (Fritzsch and Sonntag, 1987), and mammals (Gacek, 1974;Labandeira Garcia et al, 1983;Miyazaki, 1985;Murphy et al, 1986), the trochlear nucleus is composed of both ipsiand contralaterally projecting neurons. However, in salamanders (Naujoks-Manteuffel et al, 1986), stargazers (Leonard and Willis, 1979), the weakly electric fish Gnathonemus petersii (Szabo et al, 1987), and cartilaginous fish, the trochlear motoneurons are reported to innervate only the contralateral superior oblique muscle.…”
Section: Distribution Of Oculomotor and Trochlear Motoneuronsmentioning
confidence: 99%
“…The innervation pattern of these muscles has been studied by using modern neuroanatomical methods in representatives of the major jawedvertebrate lineages (Matesz and Székely, 1977;Luiten and Dijkstra-de Vlieger, 1978;Rosiles and Leonard, 1980;Heaton and Wayne, 1983;Labandeira et al, 1983;Porter et al, 1983;Graf and Brunken, 1984;Graf and McGurk, 1985;Graf and Baker, 1985;Naujoks-Manteuffel et al, 1986;Evinger et al, 1987;Szabo et al, 1987;BarbasHenry and Lohman, 1988;von Bartheld, 1992). These studies have shown that the six eye muscles are innervated by motoneurons distributed in three motonuclei: The oculomotor nucleus innervates the superior, inferior, and medial recti, as well as the inferior oblique.…”
mentioning
confidence: 99%
See 1 more Smart Citation